The issue of al-hawaij al-asliyyah (basic needs) and its implementation on zakat of income in Malaysia: a content analysis between Mazahib (Muslim Jurist Sects) - Husna Husain (Tanjong Malim, 2021)
The issue of al-hawaij al-asliyyah (basic needs) and its implementation on zakat of income in Malaysia: a content analysis between Mazahib (Muslim Jurist Sects) by Husna Husain